Assessing the Situation of Subjective Well-being among Iranian Youth - Karam Habibpour Gatabi (فصلنامه رفاه اجتماعی, 2022)
Introduction: Considering the failure of the objective approach in measuring youth well-being and the discourse turn of social policy towards subjective well-being, the present article, after conceptualizing subjective well-being, evaluates its situation among Iranian youth. Method: The present article is a quantitative secondary analysis of the data of the "National Survey of the Social, Cultural and Moral Status of Iranian Society" (2016) among young people aged 18 to 29 living throughout the country. Findings: Firstly, the subjective welfare of young people in many components is unfavorable. Second, the subjective welfare of young people is more unfavorable than other age groups; compared to others (30-49 years, 50 years and older), Iranian youth value higher preference, such as wealth, position, and fame; they have less belief in the existence of judicial and professional justice; they also have a more negative assessment of the welfare of society; they Evaluate the life situation in the past as more negative and the future situation as more positive; they feel less freedom, happiness, security, and national belonging; they have less belief in the prevalence of legalism and the realization of citizenship in society; finallu, they agree with a fundamental change in the current state of society. Discussion: The findings indicate that although the low level of subjective welfare among young people is a pervasive pattern with other age groups, but its lower level compared to others indicates an unfavorable state of subjective welfare in this group.